2012
DOI: 10.1002/jbmr.1562
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent progenitors resident in the skeletal muscle interstitium exhibit robust BMP-dependent osteogenic activity and mediate heterotopic ossification

Abstract: Heterotopic ossification is a debilitating condition that can result from traumatic injury, surgery, or genetic disease. We investigated the cellular origins of heterotopic skeletogenesis in the mouse using lineage tracing and bioassays of heterotopic ossification based on intramuscular transplantation. We identify, characterize and purify a tissue-resident stem/progenitor cell population that exhibits robust osteogenic potential and represents a major cell-of-origin for heterotopic ossification. These progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
369
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(394 citation statements)
references
References 54 publications
22
369
1
2
Order By: Relevance
“…On the surface, as noted above, it appear that groups have claimed widely disparate progenitors ranging from those from the nerve described in this manuscript, to endothelial cells [4], or progenitors residing in muscle [5]. However, as shown in the model of HO presented in Figure 7, each of these precursors or cells very much like them, is present during HO.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…On the surface, as noted above, it appear that groups have claimed widely disparate progenitors ranging from those from the nerve described in this manuscript, to endothelial cells [4], or progenitors residing in muscle [5]. However, as shown in the model of HO presented in Figure 7, each of these precursors or cells very much like them, is present during HO.…”
Section: Discussionmentioning
confidence: 61%
“…Although these reports do not agree on its origin, surprisingly they agree on several markers associated with the osteoprogenitor phenotype. These markers include PDGFRα, Tie-2, and SP7 [4, 5, 7]. Even studies of human osteoprogenitors involved in HO induced by traumatic injury, although passaged in vitro , confirm the presence of these markers on the cells [810].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of PDGF receptors as a marker of mesenchymal cells closely associated with the vasculature correlates with work conducted by Wosczyna et al (2012). This work showed that a population of non-endothelial Tie2 + PDGFRα + Sca-1 + cells in the muscle interstitium was found to be consistently incorporated into chondrogenic and osteogenic lesions [94]. However, the expression of PDGFα also draws a direct comparison with bone marrowderived pericyte progenitors (PDGFRα + Sca-1 + ) previously identified by Uezumi et al (2010) [62] (see Table 1).…”
Section: Endoderm Endothelial Cellsmentioning
confidence: 66%
“…For example, a study by Kirton et al (2007) has shown that the chondrogenic differentiation pathway of pericytes can be activated by Wnt/betacatenin signalling in the presence of TGF-β3 [98]. Additionally, a recent study by Kan et al (2013) identified that cells presenting the glutamate transporter GLAST were found to contribute to the formation of ectopic bone, and that these GLAST + cells appeared to be distinct from the Tie2 + population identified by Woscyzna et al (2012) [94]. Pericyte populations have been shown to express GLAST [99], and consequently this information further highlighted the potential role of these cells during HO.…”
Section: Neural Crest Pericytesmentioning
confidence: 99%
“…There have been publications suggesting that osteoprogenitors are derived from either mesenchymal stem cells in the bone marrow [29] or from the interstitial cells between the muscle fibers [45] or from fully differentiated endothelial cells [19], which then undergo an endothelial to mesenchymal transition [18]. It has also been suggested that the osteoprogenitors can be found in the circulation [39].…”
Section: Introductionmentioning
confidence: 99%